sistem informasi penjualan pada toko raja vapor gebog berbasi web dengan metode cross selling: sistem informasi penjualan pada toko raja vapor gebog berbasi web dengan metode cross selling - ERVAN PANGESTU (LPPM Universitas Merdeka Madiun, 2023)
Right Now Raja Vapor Gebog its sales are still dependent on direct sales. That is, promoting products to customers by coming directly to the store introduced products using makeshift media. With the system running still using the manual way in today's fierce competition, it is difficult to achieve the development of the company. From this problem, Raja Vapor Gebog needs to make changes to achieve these goals. One of the solutions offered to overcome these problems is to create a sales system website. For that in sales at Raja Vapor using the method of cross selling where when the buyer buys the desired item then the seller will offer a product that is felt to have a relationship with the product that the buyer wants to buy. With the aim of this system application can help customers and owners to facilitate each other in making transactions. The application will be built using waterfall development method by analyzing the needs using observation and interview method. System design is UML (Unified Modeling Language), So it can be applied using a responsive web with the creation of applications using PHP programming language and MYSQL database. Keywords: Shop; Sale; Cross Selling; Waterfall.